Geração espontânea e evolução química gradual em livros didáticos do ensino fundamental - PANTOJA, Ana Laura Pureza (Universidade Federal de Mato Grosso, 2022)
Origin of Life, as curricular content, is a controversial topic. Knowledge from various areas supports several hypotheses and plausible scenarios to explain how life originated on Earth, making room for the conflicts that exist in this matter, in addition to expressing characteristics of the nature of scientific knowledge. It is in this perspective that the approach can be linked with the History and Philosophy of Science (HPS), so that views of science that refer to the linearity of knowledge construction and the absence of conflicts are not reinforced. The discourse analysis proposed by Michel Foucault can be used as an analytical device to think about the approach of History and Philosophy of Science recommended in textbooks of basic education. Therefore, this work aims to see which discourse(s) go about the theories on the school content “Origin of Life”, strictly in relation to the theories of Spontaneous Generation and Gradual Chemical Evolution, in the elementary school textbooks for the 7th grade. The analysis indicates that the theories of Gradual Chemical Evolution and Spontaneous Generation are recurrent in textbooks with a positivist historiographical aspect, composing statements that establish the potential circulation and legitimation of scientific knowledge.